An Unusual Presentation of a Nodular Hidradenoma: A Case Report - Fatimah, Mehjabeen; Jameel Ahmed, Momin Afia; Alam, S Shah; Malik, Rabia (International Journal of Human and Health Sciences (IJHHS), 2023)
Hidradenoma also called nodulocystic hidradenoma, Clear cell hidradenoma or acrospiroma is a rare benign epithelial tumor mostly occurring in adult females. It usually appears as a single, slow enlarging, well-circumscribed, freely movable, firm, and nontender cutaneous lesion commonly seen on the scalp, face, anterior trunk, and proximal limbs. Less commonly seen in the distal limb. An 18-year-old female patient visited the Outdoor Patient Department (OPD) of the hospital of the National Institute of Unani Medicine (NIUM), Bangalore, Karnataka, India; with chief complaints of swelling in the right lower leg for 3 months. This swelling was insidious in onset, and gradually enlarged from a small papule to golf ball size, the shape was nearly hemispherical. The patient consulted a general practitioner where FNAC was done, there was serous discharge from the swelling. It was a case of nodular hidradenoma having an unusual presentation as black colour with brownish hue having an unusual larger size, ulcerated surface with serous discharge at the right lower limb. Wide surgical excision with appropriate margins to prevent local recurrence was done. After excision collagen dressing done on weekly basis for 5-6 weeks. Routine follow-up 3, 6 and 12 months later showed no signs of recurrence. Nodular hidradenoma is usually located over the head, neck, and trunk. In our case, the lesion was present in the lower limb and the presence of an unusually large tumor mass, leading to serous discharge, makes our case even more interesting. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 344-347